Electro-osmotic transport of a Williamson fluid within a ciliated microchannel with heat transfer analysis. (May 2023) - Imran, Ali; Raja, Muhammad Asif Zahoor; Shoaib, Muhammad; Zeb, Muhammad; Nisar, Kottakkaran Sooppy
Abstract: A novel theoretical model is devised for electro osmotic flow of Williamson fluid model by incorporating heat transfer phenomena in a micro ciliated channel. The physical fluid model is designed by exploiting the renowned Debye–Huckel, long wavelength small Reynolds number approximation. The exact expression for Poisson–Boltzmann equation is obtained to find the analytical solution for axial velocity, pressure gradient, temperature and stream functions comprehensively by using perturbation technique. Whereas, transverse velocity and pressure rise profile are explored numerically through the MATHEMATICA software infrastructure. The variations of paramount significant parameters on the velocity distribution, temperature, pressure gradient and pressure rise per wavelength are demonstrated graphically. It has been investigated that axial velocity profiles escalates with enhancing Weissenberg, electro-osmotic, mobility of medium parameter, while dual behavior is recorded for the case of traverse component of velocity. Cilia plays a crucial role in ductus efferentes and assumed to transfer sperm through the rete testis to the epididymis. Besides above mentioned application cilia like actuators serve in micro-mixers to regulate the flow in bio-sensors and in various drug-delivery mechanism.